Bioprosthetic valve fracture during valve-in-valve transcatheter aortic valve replacement. Issue 3 (2nd July 2020) - Hamandi, Mohanad; Nwafor, Ikenna; Hebeler, Katherine R.; Crawford, Alexander; Lanfear, Allison T.; Schaffer, Justin; Al-Azizi, Karim; Potluri, Srinivasa; Brinkman, William T.; Harrington, Katherine; Szerlip, Molly; DiMaio, J. Michael
Abstract: Transcatheter aortic valve replacement (TAVR) valve-in-valve (VIV) therapy has been approved for select patients with surgically inoperable bioprosthetic valves that need replacement. Bioprosthetic valve fracturing (BVF) used in conjunction with VIV TAVR can reduce transvalvular gradients and increase the aortic valve area. Twelve patients who underwent BVF VIV TAVR at a single center were retrospectively analyzed. Measurements of hemodynamics and aortic valve area were performed at baseline, after VIV TAVR, after BVF, and at 30-day follow-up. The mean Society of Thoracic Surgeons Predicted Risk of Mortality score was 7.12 ± 3.5%, with 75% of patients deemed high risk by the heart team. Mean gradients decreased from 44 mm Hg to 15 mm Hg following VIV TAVR, and to 7 mm Hg following BVF. The mean aortic valve area increased from 0.6 cm 2 to 1 cm 2 following VIV TAVR, and to 1.3 cm 2 following BVF. There were no postoperative permanent pacemaker implantations or vascular complications, and at 30 days, only one patient had died. While we report intraoperative mortality, BVF with VIV TAVR can be performed to reduce transvalvular gradients and increase effective aortic valve area in high-surgical-risk patients with failed bioprosthetic valves.